Safety and efficacy of directly‐acting antiviral therapy for chronic hepatitis C virus in elderly people. Issue 4 (21st December 2021) - De Santis, Adriano; Maggi, Daniela; Lubrano Lobianco, Federica
Abstract: Introduction: In Italy, the prevalence of hepatitis C virus (HCV) infection is higher in the elderly, although the efficacy and safety of treatment in this population has not been extensively studied. Moreover, little is known about how much pharmacological interaction affects eligibility to treatment and to what extent the treatment affects subsequent outcomes. Methods: We retrospectively analyzed the efficacy and safety of directly acting antivirals (DAAs), drug‐to‐drug interactions, and post‐treatment outcomes in 138 patients with HCV aged 70 years or older, who were consecutively treated in our center between 2015 and 2020. Results: The mean age was 77 years old (range = 70–95 years old). The Cumulative Illness Rating Scale of pretherapy severity was classified as moderate to severe in 65% of patients. Fifty‐five patients (40%) presented compensated cirrhosis, eight of which were complicated by hepatocellular carcinoma (HCC) and all were cured before treatment. One hundred two patients (74%) were taking two or more drugs (range = 0–5 concomitant drugs registered) and in 29 patients (21%) we found potential drug‐to‐drug interaction. In 11 of those 29 patients (38%), we were forced to change the chronic therapy, when all therapeutic regimens were equal in terms of efficacy and interactions, to avoid potentially serious drug interactions. One serious adverse event occurred in our sample population (i.e., diverticular bleeding due to interaction with direct oral anticoagulants [DOACs]), whereas mild side effects occurred in 37% of patients. The undetectability of HCV RNA at the end of treatment was achieved in 97% of patients, whereas a sustained virological response (SVR) 12 and SVR 24 were obtained in 98% of patients. When comparing pretherapy with post‐therapy data, after a medium follow‐up of 15 months (median = 1 year, minimum = 2 months, and maximum = 4 years), we observed a reduction in the incidence of episodes of liver decompensation in patients with cirrhosis and a slight increase in the incidence of HCC (with 6 recurrent and 5 de novo HCC), diagnosed within 13 months from the end of therapy. In all patients, we found a significant improvement in all ultrasound variables and a significant reduction in the elastographic measurements. No significant differences in outcomes were observed dividing the population into patients aged ≥ 80 and < 80 years old. Conclusions: Directly acting antiviral therapy was found to be safe and effective in elderly people, and, despite the large number of concomitant drugs, pharmacological interactions appeared to not affect the adherence to therapy or the incidence of adverse events. Side effects were mostly independent from the type of DAA used and from the burden of comorbidity. In long‐term follow‐up, the benefit of DAA therapy mainly concerned liver pathology and should be strongly advised in patients with cirrhosis. The therapy was found to not affect extrahepatic comorbidities but allowed to end follow‐up in noncirrhotic patients with savings in terms of resources. Finally, patients should not be excluded based on age if they have a good performance status. Abstract : We retrospectively analyzed data of 138 HCV patients aged 70 years or older, who were consecutively treated in our center between 2015 and 2020. We found out that in a real‐life population, HCV treatment is safe (with only a few potential drug‐to‐drug interactions that require management and few adverse events), effective (98% SVR at 12 weeks), and useful (it reduce decompensating events in cirrhotics and ameliorates prognostics score and clinical parameters).